2019
DOI: 10.1021/acsami.9b09681
|View full text |Cite
|
Sign up to set email alerts
|

Submicron Size Schottky Junctions on As-Grown Monolayer Epitaxial Graphene on Ge(100): A Low-Invasive Scanned-Probe-Based Study

Abstract: We report on the investigation of the Schottky barrier (SB) formed at the junction between a metal-free graphene monolayer and Ge semiconductor substrate in the as-grown epitaxial graphene/Ge(100) system. In order to preserve the heterojunction properties, we defined submicron size graphene/Ge junctions using the scanning probe microscopy lithography in the local oxidation configuration, a low-invasive processing approach capable of inducing spatially controlled electrical separations among tiny graphene regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 61 publications
1
13
0
Order By: Relevance
“…Therefore, the dark current under a low reverse bias (from 0 V to −2 V) is much lower than under a low forward bias (form 0 V to +2 V), as shown in Figure 4 b,c. It is noteworthy that the SBH tunable behavior of the camphor-based CVD graphene/p-Si heterostructure is consistent with the numerous study results of the conventional CVD bilayer graphene/Si heterostructures reported previously [ 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Measurement Results and Discussionsupporting
confidence: 90%
“…Therefore, the dark current under a low reverse bias (from 0 V to −2 V) is much lower than under a low forward bias (form 0 V to +2 V), as shown in Figure 4 b,c. It is noteworthy that the SBH tunable behavior of the camphor-based CVD graphene/p-Si heterostructure is consistent with the numerous study results of the conventional CVD bilayer graphene/Si heterostructures reported previously [ 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Measurement Results and Discussionsupporting
confidence: 90%
“…Consequently the graphene/Ge system has recently attracted a great deal of interest both in materials science [8][9][10][11] and device physics [12][13][14]. Previous work has demonstrated that the Ge(001) surface forms high-index facets upon graphene synthesis, making the system unsuitable for further processing [12,15,16].…”
mentioning
confidence: 99%
“…The location of the vacancy is highlighted by the black circle in Figure 4a,b. As known in the literature [14,[26][27][28][29],…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The attractiveness of graphene integration into CMOS technology arises from a wide variety of potential applications, including photodetectors and modulators for the NIR regime 27 29 or passivation layers 17 , 30 . Hereby, different Ge platforms, like Ge on Si 31 , 32 or Ge on insulator 33 , 34 are used.…”
mentioning
confidence: 99%